Ruang dan Identitas: Pendekatan Arsitektur Neo-Vernakular dalam Perancangan Pusat Kebudayaan Riau–Lingga di Kabupaten Lingga - Avisalvizi; Muhammad Rijal; Indra Kuswoyo (JALUR: Journal of Architecture, Landscape & Urban Design, 2026)
This study examines the application of Neo-Vernacular Architecture principles in the design of the Riau-Lingga Cultural Center as a strategy to reinforce local identity amid the tide of modernization and shifting cultural values. The main objective of this research is to formulate a design approach that can revive the values, elements, and characteristics of traditional architecture of the Riau-Lingga Sultanate in the form of contemporary buildings that are relevant to today's needs. The method used is Research by Design, which includes pre-design stages of cultural data collection, vernacular element analysis, functional studies, and site context; followed by design exploration through mass studies and spatial experiments; and concluded with design evaluation of its success in representing local identity. The research findings show that the application of Neo-Vernacular principles, such as the use of local materials, climate responsiveness, reinterpretation of traditional roof forms, spatial hierarchy, the concept of stage buildings, verandas, and contextual massing, is capable of translating the cultural values of the Riau-Lingga Malay into a modern architectural form that remains rooted in tradition. Contemporary building technology is also selectively integrated to enhance functionality and comfort without compromising local character. Furthermore, community involvement in the design process strengthens the building's social and cultural relevance. This study concludes that the Neo-Vernacular Architecture approach effectively bridges tradition and innovation, and has the potential to make the Riau-Lingga Cultural Center a symbol of cultural regeneration and a reinforcement of Malay identity in Lingga Regency.